Divergence among local populations of Eugenia dysenterica in response to edaphic patterns and spatial distribution - Telles, Mariana Pires de Campos; Silva, Rossana Serrato Mendonça; Chaves, Lázaro José; Coelho, Alexandre Siqueira Guedes; Filho, José Alexandre Felizola Diniz (Pesquisa Agropecuaria Brasileira, 2001)
The domestication and management of native plant species for uses in agricultural systems is usually constrained by the absence of knowledge about genetic variability, population structure and evolutionary processes involved in population differentiation in geographic space. A full understanding of these patterns and processes implies in analyzing multiple characters. In this paper, differentiation among ten local populations of Eugenia dysenterica DC. from Southeastern region of Goiás state, Central Brazil, was analyzed. Mantel tests were used to evaluate the relationships between genetic (eight loci from isozymes) and phenotypic (morphological and demographic characters) patterns of population differentiation, in relation to spatial distribution and edaphic differences among regions. The results from Mantel's tests suggested that the main factor acting on genetic differentiation is the geographic distribution of local populations, in a stochastic model that balances local drift within local population and short-distance gene flow among them. The phenotypic differentiation, on the other hand, is better explained by edaphic patterns and also by the geographic distribution. These results support the idea of neutral (or quasi-neutral) evolutionary processes in isozymic markers and shows that genetic divergence among local populations is highly structured in geographic space, independently of variations in edaphic patterns and phenotypic variation.
Keywords: isoenzymes; phenotypes; genetic variation; environmental factors